Evaluasi Kelayakan Usaha Produksi Pupuk Cair Organik Berbasis Urine Kelinci (Studi Kasus: Joglo Tani Indonesia): Indonesia - Utami, Sri Sari; Wicaksono, Setyoadi (UII, 2024)
Organic liquid fertilizer, particularly that derived from rabbit urine, plays a vital role in supporting plant growth while simultaneously addressing waste management challenges. This study evaluates the economic potential and feasibility of producing organic liquid fertilizer from rabbit urine, with a focus on key economic indicators. To assess the feasibility of the business, the Revenue-Cost Ratio (R/C ratio), Break-Even Point (BEP), and Return on Investment (ROI) were calculated. The findings reveal an R/C ratio of 2.591, indicating significant profitability. The break-even point is reached at a price of IDR 11,575.15 per liter, with a minimum production volume of 78.86 liters required to cover costs. Furthermore, the ROI is calculated at 159.1%, demonstrating that investment in the production of liquid organic fertilizer from rabbit urine offers considerable financial returns. Despite its promising potential, Joglo Tani faces several challenges, including suboptimal agricultural land conditions, limited knowledge among farmers, and complexities in the export licensing process. To ensure the sustainable development of this business, targeted strategies are essential, such as providing training programs to enhance farmers’ knowledge and establishing partnerships to streamline export licensing procedures. The production of liquid organic fertilizer from rabbit urine holds significant promise for advancing sustainable agricultural practices, boosting economic growth, and promoting effective waste management solutions.